Significance of hepatic preneoplasia in risk identification and early detection of neoplasia - Bannasch, Peter; Haertel, Thomas; Su, Qin (Toxicologic pathology, 2003)
Among the different types of liver tumor, hepatocellular neoplasms predominate by far in both animals and man. Consequently, preneoplastic foci of altered hepatocytes (FAH), preceding both hepatocellular adenomas and carcinomas, represent the most prevalent form of hepatic preneoplasia observed in animals for a long time, and identified in human chronic liver diseases associated with, or predisposing to, hepatocellular carcinomas more recently. Morphological, microbiochemical, and molecular biological approaches in situ revealed striking similarities in specific changes of the cellular phenotype of preneoplastic FAH developing in experimental and human hepatocarcinogenesis, irrespective of whether this was elicited by chemicals, hormones, viruses or radiation. The advantage of using FAH for risk identification (aiming at primary cancer prevention) in long-term and medium-term carcinogenesis bioassays has been well documented, but quantitative morphometric approaches appear to be indispensable for an appropriate evaluation of both bioassays. The detection of phenotypically similar FAH in various animal models and in humans prone to develop or bearing hepatocellular carcinomas favors the extrapolation from data obtained in animals to humans. Moreover, the recently reported frequent finding of FAH in fine-needle biopsies of patients suffering from chronic liver diseases opens new perspectives for secondary prevention of human hepatocellular carcinoma.